Formation of retromer transport carriers is disrupted by the Parkinson disease‐linked Vps35 D620N variant. (22nd January 2021) - Cui, Yi; Yang, Zhe; Flores‐Rodriguez, Neftali; Follett, Jordan; Ariotti, Nicholas; Wall, Adam A.; Parton, Robert G.; Teasdale, Rohan D.
Abstract: Retromer core complex is an endosomal scaffold that plays a critical role in orchestrating protein trafficking within the endosomal system. Here we characterized the effect of the Parkinson's disease‐linked Vps35 D620N in the endo‐lysosomal system using Vps35 D620N rescue cell models. Vps35 D620N fully rescues the lysosomal and autophagy defects caused by retromer knock‐out. Analogous to Vps35 knock out cells, the endosome‐to‐trans‐Golgi network transport of cation‐independent mannose 6‐phosphate receptor (CI‐M6PR) is impaired in Vps35 D620N rescue cells because of a reduced capacity to form endosome transport carriers. Cells expressing the Vps35 D620N variant have altered endosomal morphology, resulting in smaller, rounder structures with less tubule‐like branches. At the molecular level retromer incorporating Vps35 D620N variant has a decreased binding to retromer associated proteins wiskott–aldrich syndrome protein and SCAR homologue (WASH) and SNX3 which are known to associate with retromer to form the endosome transport carriers. Hence, the partial defects on retrograde protein trafficking carriers in the presence of Vps35 D620N represents an altered cellular state able to cause Parkinson's disease. Synopsis: Retromer plays a critical role in orchestrating the sorting and trafficking of transmembrane receptors within the endosomal system. We demonstrate that Parkinson disease‐linked Vps35 D620N variant is defective in the formation of retromer‐mediated CI‐M6PR‐loaded endosomal transport carriers that are tethered at the trans‐Golgi network by GCC88. We also demonstrate that the endosomal recruitment of proteins associated with this retrograde trafficking pathway, SNX3 and WASH complex subunit FAM21 is impaired in the presence of Vps35 D620N variant.